Changes in blood serum protein profile in low-yielding ewes during the periparturient period - Veronika Glembova; Csilla Tóthova; Veronika Oršuľakova; Oskar Nagy (Open Veterinary Journal)
Background: In high-yielding dairy ewes, metabolic and reproductive processes occurring around the time of parturition and during lactation initiation are accompanied by several changes in blood biochemical parameters, including those related to protein metabolism. However, little is known about the distribution of serum proteins throughout the peripartum period in ewes without higher economic productivity.